The Impact of Good Corporate Governance (GCG) Implementation on Earnings Management in Manufacturing Companies in the Food and Beverage Subsector Listed on the Indonesia Stock Exchange - Maharani Wulandari; Ari Agung Nugroho; Darman Saputra (Garuda Prestasi Nusantara Consulting, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) implementation on earnings management in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the period 2020–2024. The GCG mechanisms examined include the independent board of commissioners, audit committee, institutional ownership, managerial ownership, and board of directors. The dependent variable, earnings management, is measured using the discretionary accruals approach based on the Dechow et al. (1995) model. The study employs a quantitative approach with panel data from 32 sample companies selected through purposive sampling, yielding 160 observations. Analysis was conducted using panel data regression with EViews 13 software, with the Common Effect Model (CEM) selected as the appropriate model. The results indicate that partially, the independent board of commissioners, institutional ownership, and managerial ownership have a significant effect on earnings management, while the audit committee and board of directors do not. Simultaneously, all GCG variables have a significant effect on earnings management with an Adjusted R-squared value of 53.18%.